Silencing Arbuscular Mycorrhizal Fungal Gene Using Chitosan Nanoparticle-Mediated dsRNA Delivery System - Chumei Yan; Yuemin Wang; Qianhuang Guo; Hongjuan Huan; Siwei Wang; Xiaoning Fan; Xianan Xie (Bio-Protocol)
It has been discovered that many phytopathogenic fungi can absorb exogenous double-stranded RNAs (dsRNAs) to silence target genes, inhibiting fungal growth and pathogenicity for plant protection. In our recent report, the beneficial arbuscular mycorrhizal (AM) fungi are capable of acquiring external naked dsRNAs; however, whether the dsRNAs can be delivered into AM fungi through nanocarriers remains to be investigated. Here, we introduce a simple and advanced method for in vitro synthesizing chitosan (CS)/dsRNA polyplex nanoparticles (PNs) to silence the target gene in the AM fungus Rhizophagus irregularis. This method is straightforward, requiring minimal modifications, and is both efficient and eco-friendly, offering potential for rapid application in elucidating gene functions in AM fungi.